(untitled) - Taut, Bruno (London, 1938)
First Edition. Bruno Taut (1880-1938) was not a Japanologist nor an art historian specialising on East Asia; he was a successful modern architect of housing developments in Berlin in the 1920's. When Taut emigrated to Japan in 1933, he had expected to experience the celebrated eminent culture of the country; he also hoped to work as an advisor to architects or institutions dealing with city planning and housing development. As a well reputed modern German architect who was invited to give public lectures that received much publicity, Taut, after his arrival in Japan in May 1933, was asked to write about his first impressions of the country, no matter whether they were positive or negative. His book Nippon mit europäischen Augen gesehen, compiled in July 1933 and published in Spring 1934 soon became a big success. In all, he finished four books, two published in Japanese, Nippon Seen with European Eyes (1934), Japanese Arts Seen with European Eyes, translated as Nippon bunka shi kan, A Personal View on Japanese Culture (1936), Fundamentals of Japanese Architecture in German and English (1936), and Houses and People of Japan (1937) in English.
Keywords: Kiến trúc,Architecture; Nhật Bản,Japan